Temperature-Dependence of Mixing Properties of Cu-Ti Liquid Alloy - Sah, D.K.; Adhikari, D.; Yadav, S.K. (Adhyayan Journal, 2023)
In this study, the temperature-dependence of thermodynamic and surface properties of Cu-Ti binary liquid alloy were studied. In thermodynamic properties, excess Gibbs free energy of mixing, enthalpy of mixing, excess entropy of mixing, and activity of the system were computed at 1873 K. The surface properties were analyzed by computing the surface tension and surface concentration of the system. Thermodynamic properties were computed in the framework of the Redlich-Kister polynomial, and the surface properties were computed using the Butler model. At its melting point, the system exhibited a tendency for the formation of compounds, and as the Cu concentration was increased, the surface tension of the system gradually decreased. The excess Gibbs free energy of mixing, activity and surface tension of the system were also computed at different temperatures, in the range 1873-2173 K. With the increase in temperature of the system, the compound forming tendency of the system gradually decreased.